Revised Chinese resident health literacy scale for the older adults in China: simplified version and initial validity testing - Wang, Yilin; Jia, Qiaoling; Wang, Haiyan; Zou, Kaiwen; Li, Lu; Yu, Bing; Wang, Li; Wang, Yanhong (Frontiers in Public Health, 2023)
ABSTRACT Objective This study aimed to develop a short version of the Chinese Resident Health Literacy Scale focused on older adults in China, and further assess the reliability and validity of this short version. Methods The data was from a cross-sectional community-based older adults health survey conducted in 2020. The total of 5829 older adults were randomly divided into two parts using for the simplification and assessment of the scale, respectively. Item Response Theory (IRT) and Differential Item Functioning (DIF) were used for item analysis and scale simplification. Cronbach’s alpha and McDonald’s omega were used to assess the reliability and three factors Confirmatory Factor Analysis (CFA) was used to assess the validity, which were compared to the original version. Moreover, Multi-group Confirmatory Factor Analysis (MCFA) was used to test the model invariance of the short version across groups of gender, age groups, level of education, and cognitive status. Results The simplified version consisted of 27 items taken from 50 original items, of them 11 items from the dimension of knowledge and attitudes, 9 items from the dimension of behavior and lifestyle, and 7 items from the dimension of health-related skills. The overall Cronbach’s alpha and McDonald’s omega were both 0.87 (95%CI: 0.86-0.88). The goodness-of-fits of CFA in simplified version were still acceptable in CFI, TLI, GFI, and RMSEA, even improved in CFI, TLI, and GFI compared to those of original version. Also, the model was stable and invariant in MCFA across gender, cognitive status, and educational level groups. Conclusion In this study, we formed a simplified instrument for measuring health literacy focused on older adults in China. This short version might be more suitable for the priority recommendation in extended tracking of the dynamic changes on the levels of health literacy in the whole life cycle in public health settings. Further research might be to identify the cut-off values to distinguish the older adults with different levels of health literacy.